Can Taste and Nudging Impact Healthy Meal Consumption? Evidence from a Lunch Restaurant Field Experiment - Linda Thunström; Jonas Nordström (Lund University, School of Economics and Management, Department of Economics, 2012)
Previous research shows that taste is one of the most important factors in determining food choices, and that food choices may be affected by "nudging". We analyze how taste, as determined by meal attributes, and nudging affects consumption of a healthy labeled meal. Our analysis is based on a field experiment in a lunch restaurant and our results imply that sales of the healthy labelled meal, and its market share, is greatly impacted by its taste. Nudging, as in order of display on the menu, does not impact sales of the healthy labelled meal in our experiment. We conclude that supplying tasty healthy meals may be key to significantly impact healthy eating, superior to other policy measures aimed at encouraging healthier food choices, such as information, nudging and food tax reforms.
Keywords: C93; D12; D83; I12; 330; healthy food consumption; taste; nudging; field experiment